Blockchain technologies in e-government services: a literature review - Abdullah, Salfarina; Alwan, Al Dulaimi Moatasem Abdulmajeed; Jusoh, Yusmadi Yah (IEEE, 2022)
The efficiency of blockchain technologies in managing transactions using distributed ledgers provides new age of government services. This enhances citizen-government transparency to establish public-sector trust by preventing fraud. However, using and adopting blockchain in e-Government context was insufficiently explored in previously published literatures. This paper systematically reviews relevant works to illustrate blockchain issues, challenges, while detecting the new directions for future research of using blockchain applications in e-Government. Discussed literatures explained that adopting blockchain applications to build e-Government services still has obvious lack in empirical evidence. Predominantly, major challenges facing blockchain adoption are summarized in scalability, flexibility and security aspects. organizationally, acceptability issues in blockchain and demanding new models of e-government are illustrated as major obstacles against the adoption. Furthermore, the lack in legislations and helping regulatory represents the major environmental obstacles against the adoption.